Morphotropic phase boundary of lead-free piezoelectric ceramics from BNT-KN system - Pisitpipathsin N. (2014)
In this research work, the investigation of the morphotropic phase boundary, physical properties and electrical properties of lead- free piezoelectric materials of bismuth sodium titanium oxide: (Bi 0.5Na0.5TiO3 (BNT) and potassium niobium oxide : KNbO3 (KN) in the ceramic system of (l-x)BNT- XKN where X= 0.00, 0.03, 0.05, 0.08, 0.10 and 0.15 by modified mixed oxide method was carried out. The BNT and KN powders were prepared separately using calcination technique with optimum calcination temperature for producing both BNT and KN powders of about 800°C. XRD results revealed that the BNT-KN ceramics with low KN content of X less than 0.05 contain ferroelectric perovskite phase with rhombohedral symmetries while the higher KN content ceramics have mixed symmetries between rhombohedral and orthorhombic. >From the evidences including phases, microstructures and dielectric data of the BNT-KN ceramics, it may be assumed that the morphotropic phase boundary may be at around the composition of X = 0.05. © 2008 Trans Tech Publications, Switzerland.